Assessing an effective collaboration in higher education: A study of students’ experiences and challenges on group collaboration - Lailiyah, Malikhatul; Setiyaningsih, Lian Agustina; Wediyantoro, Prilla Lukis; Yustisia, Karlina Karadila (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2021)
Studies emphasize that collaboration remains an essential part of learning and working in the 21st century. This study seeks to report on the group collaboration of higher education students. Using Explanatory sequential mixed method design, this study tried to discuss the students’ experiences and challenges on group collaboration environment in the online learning cases. Adopting  Razmerita and Kirchner's (2014) questionnaire, 287 students involved in this study. The result indicated that overall students performed positive perception on group collaboration. In addition, to have deep analysis, 15 students were interviewed. This study contributes to an understanding of how students perceived collaboration and how they explain the obstacles recognized in their classes.DOI: 10.26905/enjourme.v6i2.6971